การพัฒนารูปแบบการเรียนการสอนภาษาตามทฤษฎีภาษาศาสตร์สังคมและแนวคิดการเรียนรู้จากประสบการณ์เพื่อเสริมสร้างความแวดไวทางวัฒนธรรมสำหรับนักเรียนมัธยมศึกษา - หนักทอง, พจนีย์; ชุษณะโชติ, ฤดีรัตน์; ม้าคนอง, อัมพร (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2019)
The purpose of this research was to develop a language instructional model based on sociolinguistic theory & experiential learning approach to enhance cultural sensitivity of secondary school students & to evaluate the effectiveness of the developed instructional model. The sample was 37 Mathayom 5 students & they were selected by using purposive r&om sampling. The time series design which took 16 weeks of the experiment was implemented in this research. The research instrument was the Cultural Sensitivity Test for Secondary Students. The data were analyzed by using the arithmetic mean, the st&ard deviation, & the dependent t-test. The findings of this study revealed that the principles of the instructional model are to create the bridge between learners’ prior experience concerning language & culture & their new experience in order to highlight the value & the importance of their learning & make it more meaningful to them. The language learning happens through social interaction in multicultural situations that provides safe & nurturing atmosphere for learners & when learners interact with people from various socio-cultural contexts & share their views towards what they have done, they tend to realize cultural differences between people. This instructional model consists of 5 stages; 1) reexperience 2) react 3) reflect 4) refine & 5) refer. In addition, the result of the effectiveness of the developed instructional model demonstrated that the sample group had significantly higher post-test mean scores than the pre-test at the level of .05 both in overall score & scores of each component of cultural sensitivity.